Case Report: A False Negative Case of Anti-Yo Paraneoplastic Myelopathy - Bartley, Christopher M.; Parikshak, Neelroop N.; Ngo, Thomas T.; Alexander, Jessa A.; Zorn, Kelsey C.; Alvarenga, Bonny D.; Kang, Min K.; Pedriali, Massimo; Pleasure, Samuel J.; Wilson, Michael R. (Frontiers in Neurology, 2021)
The development of autoimmune antibody panels has improved the diagnosis of paraneoplastic neurological disorders (PNDs) of the brain and spinal cord. Here, we present a case of a woman with a history of breast cancer who presented with a subacute sensory ataxia that progressed over 18 months. Her examination and diagnostic studies were consistent with a myelopathy. Metabolic, infectious, and autoimmune testing were non-diagnostic. However, she responded to empirical immunosuppression, prompting further workup for an autoimmune etiology. An unbiased autoantibody screen utilizing phage display immunoprecipitation sequencing (PhIP-Seq) identified antibodies to the anti-Yo antigens cerebellar degeneration related protein 2 like (CDR2L) and CDR2, which were subsequently validated by immunoblot and cell-based overexpression assays. Furthermore, CDR2L protein expression was restricted to HER2 expressing tumor cells in the patient's breast tissue. Recent evidence suggests that CDR2L is likely the primary antigen in anti-Yo paraneoplastic cerebellar degeneration, but anti-Yo myelopathy is poorly characterized. By immunostaining, we detected neuronal CDR2L protein expression in the murine and human spinal cord. This case demonstrates the diagnostic utility of unbiased assays in patients with suspected PNDs, supports prior observations that anti-Yo PND can be associated with isolated myelopathy, and implicates CDR2L as a potential antigen in the spinal cord.